2020
DOI: 10.31002/metathesis.v4i1.2264
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotypes in Students’ English Writing

Abstract: <p class="AbstractText">Gender stereotypes are guidelines by which a particular gender group behaves as expected based on the existing ideology in the community. Gender stereotypes that are perpetuated by popular culture usually marginalize women, following patriarchal ideology. This popular culture is consumed mostly by the younger generation as well as students. STIKES Nasional is an educational institution where most students are female, and most student organizations are led by female students. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The result hypothesis will be formed based on the literature review and the latest research results. According to the previous research outcome reviewed in the introduction, there is a relationship between gender stereotypes and students' L2 writing [1,3,2]. Furthermore, the previous literature also proposed the impacts of education on gender egalitarianism [4].…”
Section: Results Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…The result hypothesis will be formed based on the literature review and the latest research results. According to the previous research outcome reviewed in the introduction, there is a relationship between gender stereotypes and students' L2 writing [1,3,2]. Furthermore, the previous literature also proposed the impacts of education on gender egalitarianism [4].…”
Section: Results Hypothesismentioning
confidence: 99%
“…Firstly, the related literature review suggested the relationship between writing and the formation of gender ideology. The subjectivity in English is students as the subject tend to speak about gender through subject pronouns, such as he or she, in their writing, and gender stereotypes can be reflected in the writing materials [1]. The reason for gender stereotypes in writing through the fact that male firstness in academic writing is latent, rather than overt, forming gender bias [2].…”
Section: Research Background 1writing As a Form To Present Gender Ide...mentioning
confidence: 99%
See 1 more Smart Citation